Nickel (Ni) reduction in Sorowako post-mining soil through application of mycorrhiza Acaulospora sp. associated with Canavalia ensiformis L. - M. Akhsan Akib; Kahar Mustari; Tutik Kuswinanti; Syatrianty Andi Syaiful; Syatrawati `; Z. Kumalawati (Journal of Microbial Systematics and Biotechnology, 2019)
The nickel (Ni) content in a post-mining soil of Pomalaa mines reached 14,200 mg.kg-1 and became a limiting factor in the plant growth process. A Ni reduction in the soil by using phyto-accumulator such as Jack bean (Canavalia ensiformis L.) can be improved by combining it with arbuscular mycorrhizal (AM) fungi. The purpose of this study was to determine the effect of the mycorrhizal fungus Acaulospora sp. on the efficiency of Ni reduction by C. ensiformis. This experiment was carried out by using a randomized block design with three different treatments, include: 1) C. ensiformis without Acaulospora sp. inoculation (negative control), 2) C. ensiformis inoculated with indigenous Acaulospora sp. and 3) C. ensiformis inoculated with non-indigenous Acaulospora sp. The study was conducted in the nursery that belongs to PT. Vale Indonesia Tbk., Sorowako, South Sulawesi, Indonesia. The results showed that highest nickel accumulation was found in the root inoculated with indigenous Acaulospora sp. (9500 mg.kg-1), followed by stem (1400 mg.kg-1), leaf and pod (1300 mg.kg-1), seed (1200 mg.kg-1), and flower (1100 mg.kg-1). This study indicates that application of the indigenous Acaulospora sp. can improve C. ensiformis efficiency to reduce Ni content at Sorowako post-mining area.